Associations of sex on economic burden in patients with symptomatic obstructive hypertrophic cardiomyopathy: results from medical and pharmacy claims data - Butzner, Michael; Amonkar, Sanika; Chen, Meiling; Papademetriou, Eros; Potluri, Ravi; Liu, Xing; Abraham, Theodore (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPrevious studies of patients with symptomatic obstructive hypertrophic cardiomyopathy (oHCM) have reported worse clinical burden for female patients; whether this translates to an increase in healthcare resource use (HRU) and cost is unknown. Therefore, we evaluated the impact of sex on economic burden in symptomatic oHCM.MethodsMedical and pharmacy claims data were assessed from 2016 to 2021 to identify (ICD-10 code) adult patients with symptomatic oHCM in the United States. Generalized linear models were used to estimate HCM-related cost and generalized estimating equations for HRU [both reported as mean per-person-per-year (PPPY)] for healthcare categories: inpatient, outpatient, emergency room (ER), urgent care, and pharmacy. Cox proportional hazard regressions were used to compare differences in male and female patients with symptomatic HCM.ResultsAmong 9,490 patients with symptomatic oHCM, 5,309 (55.9%) were female. Female patients were older (64 ± 13 vs. 59 ± 14), with a higher Charlson Comorbidity Index (1.9 vs. 1.7) compared to males, respectively. After adjusting for patient characteristics, female patients had significantly greater number of HCM-related hospitalizations (0.24 vs. 0.20 PPPY, p = 0.0014), LOS (5.08 vs. 4.30 PPPY; p = 0.0235), number of outpatient visits (4.98 vs. 4.59 PPPY; p = 0.0387), and number of distinct drugs (0.59 vs. 0.55 PPPY; p = 0.0010), compared with males, respectively. In adjusted models, only HCM-related pharmacy costs were significant, with female patients having slightly higher costs compared to males ($70 vs. $61 PPPY; p = 0.0465). There were no significant differences in all-cause costs of care between male and female patients with oHCM.          ConclusionsFemale patients with symptomatic oHCM experience greater rates of HCM-related and all-cause hospitalizations and number of prescriptions, and HCM-related length of stay, outpatient visits, and pharmacy costs compared to male patients.